Digital Asset Enforcement Reform in Indonesia: A Polycentric Governance Approach - Syamsul Maarif (Yustisia, 2026)
Digital assets are growing quickly in Indonesia, which has caused a lot of legal and institutional problems, especially when it comes to settling disputes over cryptocurrencies, tokenised assets, and other blockchain-based tools. Despite regulatory recognition, there remains a critical gap between legal frameworks and effective remedies for victims, highlighting the urgency of enforcement reform. This article examines the key legal problems, including regulatory fragmentation, ambiguity in asset classification, cross-border enforcement barriers, limitations in digital forensic capacity, and weak inter-agency coordination. Using a normative-doctrinal method combined with comparative analysis of cases and regulatory developments, this study adopts a polycentric governance approach to assess how administrative, civil, and criminal enforcement pathways interact and where they fail. The findings reveal that enforcement inefficiencies occur across the entire dispute chain, leading to inadequate victim recovery, legal uncertainty, and reduced market trust. This study proposes a sequenced reform framework, including the enactment of a consolidated digital asset law with functional classification, strengthening regulatory authority with asset preservation powers, reforming insolvency law to recognise digital property, establishing standardised forensic and evidentiary protocols, and enhancing cross-border cooperation mechanisms